Avaliação da sinalização purinérgica em tecido hepático e esplênico de camundongos infectados com Toxoplasma gondii e tratados com disseleneto de difenila - Doleski, Pedro Henrique (2017)
Toxoplasmosis is a zoonosis of worldwide distribution caused by the parasite Toxoplasma gondii, which in general develops asymptomatic and chronic characteristic infection in mammals and birds. In this period, the parasite is encysted in the brain tissue, however, it is possible that the inflammatory process developed to combat the parasite may cause extracerebral damage. Among the possible organs affected by the infection are the liver and the spleen. Purine nucleotides and nucleosides and their regulation by enzymes known as nucleotidases and nucleosidases are involved in numerable physiological processes through purinergic signaling. Therefore, the objective of this work is to evaluate the effect of subcutaneous treatment with diphenyl diselenide (PhSe)2, a compound with antioxidant and immunomodulatory effects, on the purine concentration and activity of purinergic enzymes in hepatic and splenic tissue of mice infected by T. gondii (strain ME-49). For the experiment, 40 Swiss mice were divided into four groups: Group A (uninfected), Group B (uninfected and treated with (PhSe)2), Group C (infected) and Group D (infected and treated with (PhSe)2). The infection (Group C and D) was performed by the inoculation of 50 cysts of T. gondii strain ME-49. The animals of Group B and Group D received 5 μmol kg-1 of (PhSe)2 subcutaneously on the 1st and 20th day after infection. After 30 days of infection, the mice were euthanized and the samples were collected. Histopathological results revealed an inflammatory process in the hepatic and splenic tissues in mice infected with T. gondii, that is, splenomegaly and inflammatory infiltrates. The infection altered the activity of the purinergic enzymes in the liver, which are involved in the physiological control of purines. The high activity of NTPDase may be related to the reduction of high levels of ATP found in the liver, whereas the high adenosine deaminase (ADA) activity may be responsible for the low levels of adenosine found in the tissue. Likewise, the high activity of xanthine oxidase (XO) may be related to the degradation of high xanthine levels, thus raising uric acid levels observed by HPLC analysis. In the infected and untreated animals the same enzymatic changes were found in the spleen as in the liver. On the other hand, in the serum of infected animals, no alterations were found in the NTPDase enzyme, but, the activity of the 5'nucleotidase and ADA enzymes increased, which may lead to a reduction of the levels of adenosine in the bloodstream. However, (PhSe)2 was effective in reducing the damage induced by the infection, observed by histological analysis as mild inflammatory infiltrates. It was also able to alter purinergic enzymes, further elevating NTPDase activity in infected and treated animals and decreasing ADA and XO tissue activity. Possibly, these regulations are involved in the reduction of ATP levels and increase of adenosine and xanthine, a fact that was confirmed by HPLC purine analysis in the hepatic tissue. The antioxidant effects of (PhSe)2 were observed in splenic tissue, where low levels of reactive oxygen species (ROS) were observed in infected and treated animals compared to untreated infected animals. Interestingly, (PhSe)2 was not able to alter the degradation profile found in infected and untreated animals in the serum, which demonstrates its ineffective action on the bloodstream. T. gondii chronic infection is able to induce inflammatory process and physiological changes, and (PhSe)2 treatment is able to reverse such processes, it is suggested that the use of immunomodulatory agents may be beneficial against splenic injury and In animals chronically infected by T. gondii.